Capsular polysaccarides of probiotics and their immunomodulatory roles - Jing Li; Saisai Feng; Leilei Yu; Jianxin Zhao; Fengwei Tian; Wei Chen; Qixiao Zhai (Food Science and Human Wellness)
Studies have determined the immunomodulatory activities of cell-surface polysaccharides of lactic acid bacteria (LAB) and Bacteroides; however, the mechanisms, synthesis, regulation, structure, and functional links have not been systematically discussed. We first introduce the structure of the capsular polysaccharides (CPSs) of commonly studied probiotics and Bacteroides. Wzx-Wzy dependent and ATP-binding cassette (ABC) transporter-dependent pathways are the two main biosynthesis and secretion of CPS pathways. The genes known to be associated with these two pathways are mainly those associated with priming glycosyltransferase (pGT); a variable number of genes encoding for different glycosyl transferases (GTs); Wzx/Wzy-encoding enzymes related to flippases and polymerases; and ABC-transporter genes. In addition, the effects of CPSs on host immunity as well as their related underlying mechanisms are described. Surface polysaccharides on probiotics can serve as a mask to aid in their escape from attacks from the host’s immune system. In turn, they also exhibit immunomodulatory activities, such as strengthening the functions of macrophages, promoting the maturation of antigen-presenting cells, and inducing regulatory T cells. All of these effects of cell-surface polysaccharides exhibit their significant protective properties in immunocompromised diseases, such as colitis, arthritis, and dermatitis. Finally, we focused on their structure and functional links.